2023
DOI: 10.1111/ldrp.12301
|View full text |Cite
|
Sign up to set email alerts
|

The Feasibility of Using Virtual Professional Development to Support Teachers in Making Data‐Based Decisions to Improve Students’ Writing

Abstract: Rubrics can be used to give students targeted feedback on their writing and, therefore, teachers should be able to use them as a type of formative assessment to guide writing instruction. This article describes an exploratory study of how three teachers provided instruction for fourth, fifth, and seventh graders with learning disabilities and attention-deficit hyperactivity disorder in using a technology-based graphic organizer (TBGO) to compose persuasive essays. Given professional development inclusive of on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 50 publications
0
0
0
Order By: Relevance
“…All students were first asked to write a persuasive opinionbased essay in response to one of two prompts validated by previous research (Regan et al, 2023b). Examples of the prompts included:…”
Section: Study Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…All students were first asked to write a persuasive opinionbased essay in response to one of two prompts validated by previous research (Regan et al, 2023b). Examples of the prompts included:…”
Section: Study Contextmentioning
confidence: 99%
“…The vast majority included such important persuasive essay elements such as a topic sentence introducing the opinion, distinct reasons, examples to explain the reasons, summary sentence, and transition words. While this provides some important context, the quantity and quality of students' writing products is not the focus of the current study and is reported elsewhere (Boykin et al, 2019;Day et al, 2023;Evmenova et al, 2016Evmenova et al, , 2020bRegan et al, 2018Regan et al, , 2023b).…”
Section: Study Contextmentioning
confidence: 99%